Agricultural Frontier, Peasant Movements and Indigenous Peoples of Northern Nicaragua (1980-2019): De los milpas y chilotes a los auto-convocados (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
In this article I will analyze the peasant and indigenous movements of the municipalities of Wiwili and Bocay in the last 40 years, the sources were obtained through five years of intense archaeological, historical, linguistic, anthropological and sociological study in the department of Jinotega. We worked with historical documentation of the municipalities in question, the ethnographic and ethnological methods and techniques were implemented for the registration of testimonies of community leaders who were part of the counterrevolution and the Sandinista Popular Army (1981-1990). The emphasis is placed on the historical and strategic changes that peasants and indigenous people have been suffering since the 1980s, their transformation in the struggle for access to land in the 1990s, until the creation of special regions called Wangki Wihta Bukawas located in the core area of the Bosawas Biosphere Reserve and composed of three Miskitus territories such as: Miskitu Kipla Sait Tasbaika, Miskitu Indian Tasbaika Kum and Miskitu Lilamni Tasbaika Kum and a Mayangna Sauni Bu territory, all known as Government Indigenous Territorial (GTI) restored by the current Sandinista government in 2008. In the department we find a multicultural dynamic little studied by Nicaraguan anthropologists, particularly in the municipalities of Wiwili and Bocay regions severely affected and devastated by the intense fighting that developed in that territory, from the libertarian deed of Augusto C. Sandino hast to the war of 1980 and during the postwar period.
Keywords: Armed Conflict; Peasant Movements; Agricultural Frontier and Indigenous Peoples in northern Jinotega Raíces Uwe